Sentence Complexity Analysis in Selected Students’ Scientific Papers: A Closer Look on Abstract Section - Dara Mubshirah; Gumarpi Rahis Pasaribu; M. Husnan Lubis; Erikson Saragih; Rudy Sofyan (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2023)
Abstract. Abstract is an essential part of a scientific paper. However, according to the finding of researchers working in the repository at the (UIN) Ar-Raniry Banda Aceh, many students still do not comply with the rules for writing scientific papers. This study aims to analyze the types of sentence complexity in the thesis abstracts of UIN Ar-Raniry Banda Aceh students and the level of use of sentence complexity in scientific papers by students of UIN Ar-Raniry Banda Aceh. This study used a qualitative approach with descriptive and content analysis methods. The data were obtained from the Repository UIN Ar-Raniry through purposive sampling. The data were analyzed using Miles and Huberman’s method. The result shows four types of sentence complexity in abstract writing, namely simple sentence (24.58%), compound sentence (25.97%), complex sentence (26.25%,) and compound-complex Sentence (23.19 %). The level of sentence complexity in student scientific abstracts includes complex sentences containing independent clause + noun clause, independent clause + adjective clause, independent clause + noun clause + adverbial clause. This finding contributes to improving the skills of students' ability in scientific writing.Keywords: abstract writing; scientific papers; sentence complexityAbstrak. Abstrak merupakan bagian terpenting dalam sebuah karya ilmiah. Menurut temuan peneliti dari repositori UIN Ar-Raniry Banda Aceh, masih banyak mahasiswa yang tidak mematuhi aturan penulisan karya ilmiah. Tujuan penelitian ini untuk menganalisis jenis kompleksitas kalimat dalam abstrak skripsi mahasiswa UIN Ar-Raniry Banda Aceh dan tingkat penggunaan kompleksitas kalimat dalam karya ilmiah oleh mahasiswa UIN Ar-Raniry Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis deskriptif yang  menggunakan pendekatan analisis isi. Data diperoleh dari Repository UIN Ar-Raniry melalui teknik pengambilan sampel purposive. Data dianalisis dengan menggunakan metode Miles and Huberman. Hasil penelitian menunjukkan bahwa terdapat empat jenis kompleksitas kalimat dalam penulisan abstrak yang terdiri atas kalimat sederhana 24,58%, kalimat majemuk 25,97%, kalimat kompleks 26,25%, dan kalimat majemuk-kompleks 23,19%. Tingkat kerumitan kalimat dalam menulis abstrak ilmiah terdiri atas kalimat kompleks yang mengandung independent clause + noun clause, independent clause + adjective clause, independent clause + noun clause + adverbial clause. Temuan ini memberikan kontribusi untuk meningkatkan keterampilan kemampuan mahasiswa dalam menulis ilmiah.Kata kunci: kompleksitas kalimat; karya ilmiah; penulisan abstrak